Social innovation governance and the role of universities: Cases of quadruple helix partnerships in Italy - Bellandi, Marco; Donati, Letizia; Cataneo, Alessandra (Technological Forecasting and Social Change)
This paper explores the governance of social innovation throughout quadruple helix partnerships between civil society, business, government, and academic actors. Particular attention is given to the participation of universities in such partnerships as an expression of public and community engagement under broad third mission goals. Quadruple helix partnerships may favour the governance of projects aiming at social innovation, but conflicts and drawbacks can hinder the alignment of partners’ contributions. To tackle this issue, we develop a conceptual framework that points out four key phases in such governance processes: i) identification of a common nexus, ii) building of shared strategies, iii) implementation, and iv) learning feedbacks. We apply this framework to three Italian projects under the new EU Urban innovative actions’ program. Different alignment pathways and barriers in the governance process emerge and are discussed. The results show that quadruple helix partnerships for social innovation work smoothly if a solid common nexus between partners is in place. The University is used as a focal actor to understand the mechanisms underpinning each phase and the role it may play in such partnerships.
Keywords: Europe; Gouvernance; Innovation sociale; Partenariat; Quadruple helix approach; Réservé UdeM; Rôle des universités